2016
DOI: 10.1111/1348-0421.12359
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of antibiofilm compound 1 against Staphylococcus aureus biofilms

Abstract: A novel benzimidazole molecule that was identified in a small-molecule screen and is known as antibiofilm compound 1 (ABC-1) has been found to prevent bacterial biofilm formation by multiple bacterial pathogens, including Staphylococcus aureus, without affecting bacterial growth. Here, the biofilm inhibiting ability of 156 mM ABC-1 was tested in various biofilm-forming strains of S. aureus. It was demonstrated that ABC-1 inhibits biofilm formation by these strains at micromolar concentrations regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
3
15
0
1
Order By: Relevance
“…ABC-1 suppresses S . aureus protein A (SpA) expression and prevents the accumulation of polysaccharide intercellular adhesin (PIA) 19 . Therefore, it is possible that some of the hits identified from the C .…”
Section: Resultsmentioning
confidence: 99%
“…ABC-1 suppresses S . aureus protein A (SpA) expression and prevents the accumulation of polysaccharide intercellular adhesin (PIA) 19 . Therefore, it is possible that some of the hits identified from the C .…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the biofilm-elaborating ability of clinical isolates in Japan and found that TF2758, which was isolated from an atheroma, is an extremely high biofilm producer ( 17 ). Whole-genome sequencing and a microarray analysis of TF2758 discovered a spontaneous mutation in a putative transcriptional regulator gene, within a 7-gene cluster, which was expressed at markedly higher levels than in a non-biofilm-elaborating control strain.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our results, Sambanthamoorthy et al () reported the anti‐biofilm activity of benzimidazole molecules, without having the bactericidal activity except for Helicobacter pylori , against Gram‐negative and Gram‐positive bacteria pathogens (Sambanthamoorthy et al, ). Recently, at 156 ÎŒM, benzimidazole was shown to inhibit S. aureus biofilm formation without bactericidal activity by binding to the biofilm proteins (Shrestha et al, ). Another chemical molecule, 4‐(benzylamino) cyclohexyl 2‐hydroxycinnamate has shown anti‐biofilm activity (MBIC 65 ÎŒg/mL) against UTI associated staphylococcal infection (Balamurugan et al, ).…”
Section: Resultsmentioning
confidence: 99%